Propagation of Short Electromagnetic Pulses through Nonconducting Media with Electric and Magnetic Dipole Currents - Harmuth, H.F.; Lukin, K.A. (Радиофизика и радиоастрономия, 2002)
Propagation of electromagnetic signals through a non-conducting medium with very low density of neutral gas is considered with taking into account both electric and magnetic dipole currents. A new approach based on microscopic description of the medium and analytical solution of Maxwell equations in time domain has been used to solve the problem. The time delay between the signal precursor and its main lobe evaluated may be used for evaluation of either distance to a pulsar for the known medium parameters or those parameters for a given distance to the pulsar.